Family expectations on the inclusion of students with disabilities: Interfaces with the school curriculum (Research, Society and Development, 2023)
This article aims to reflect on the expectations of families of students with disabilities regarding their development and participation in the curricular activities presented in the school context, based on results from a Final Paper. As a theoretical framework, we used the contributions of Magalhães, Queiroz, Magalhães; Soares; Araújo; Soares; Oliveira, among others. Based on the recognition of the importance of the family as a fundamental agent in the child’s integral development, it is of great relevance to understand their expectations regarding their children’s learning, especially regarding children with disabilities. Based on the field research methodology, through semi-structured interviews with mothers of children with disabilities at the Progredir Municipal School, the locus of shared research, it was possible to identify some expectations of participation in the school curriculum. However, they are considered timid when analyzed in the light of the school's social function. New ways of perceiving children with disabilities must be conceived, given that these expectations, combined with conceptions about disability, can be reflected in curricular practices. Furthermore, schools must be attentive to actions that intervene in the school development and inclusion process.